Does pre‐operative counselling of the donor improve immediate and short‐term outcomes after living liver donation? – A review of the literature and expert panel recommendations. Issue 10 (9th December 2022) - Adams, Megan A.; Andacoglu, Oya; Crouch, Cara E.; de Santibañes, Martin; Jackson, Whitney E.; Jalal, Arif; Montasser, Iman F.; Rubman, Susan; Spiro, Michael; Raptis, Dimitri Aristotle; Miller, Charles; Pomfret, Elizabeth; et al.
Abstract: Background: There is some evidence in the literature to suggest that pre‐operative counselling improves pain scores postoperatively. However, it is unclear whether pre‐operative counselling of the donor improves immediate and short‐term outcomes after living liver donation. Objectives: This systematic review aimed to investigate the available quality of evidence (QOE) of pre‐operative counselling for living donors on short term outcomes, provide expert opinion, grade recommendations and identify relevant components for Enhanced Recovery after Surgery (ERAS) protocols. Data Sources: Ovid MEDLINE, Embase, Scopus, Google Scholar, and Cochrane Central. Methods: Systematic review following PRISMA guidelines and recommendations using the GRADE approach derived from an international expert panel. Endpoints were defined by the WHOQOL‐BREF scale: physical health, psychological, social relationships, and environment. PROSPERO ID: CRD42021260677. Results: Screening of 452 records and full texts led to 12 articles matching inclusion criteria, of which one was a randomized controlled trial (RCT), and 11 were observational retrospective cohort studies. A total of 933 individuals undergoing donor hepatectomy were included, of whom only 90 received dedicated perioperative ERAS protocols. Donors that received pre‐operative counselling had fewer physical symptoms post donation, lower rates of fatigue, lower rates of pain, shorter recovery times and fewer unexpected medical problems, and less anxiety post donation. Female donors had higher affective and adverse effects scores, and 50% of donors reported adverse effects to analgesia that interfered with functional activity. Receiving information about analgesic options increased perception of care among donors. Conclusions: Providing comprehensive pre‐operative counselling to living liver donors is associated with improved short‐term outcomes after donation (QOE; moderate to low I Grade of Recommendation; Strong).